Human Bone Marrow Stromal Cells: A Reliable, Challenging Tool for In Vitro Osteogenesis and Bone Tissue Engineering Approaches - Ute Hempel; Katrin Müller; Carolin Preissler; Carolin Noack; Sabine Boxberger; Peter Dieter; Martin Bornhäuser; Manja Wobus (Hindawi Limited, 2016)
Adult human bone marrow stromal cells (hBMSC) are important for many scientific purposes because of their multipotency, availability, and relatively easy handling. They are frequently used to study osteogenesis in vitro. Most commonly, hBMSC are isolated from bone marrow aspirates collected in clinical routine and cultured under the "aspect plastic adherence" without any further selection. Owing to the random donor population, they show a broad heterogeneity. Here, the osteogenic differentiation potential of 531 hBMSC was analyzed. The data were supplied to correlation analysis involving donor age, gender, and body mass index. hBMSC preparations were characterized as follows: (a) how many passages the osteogenic characteristics are stable in and (b) the influence of supplements and culture duration on osteogenic parameters (tissue nonspecific alkaline phosphatase (TNAP), octamer binding transcription factor 4, core-binding factor alpha-1, parathyroid hormone receptor, bone gla protein, and peroxisome proliferator-activated protein γ). The results show that no strong prediction could be made from donor data to the osteogenic differentiation potential; only the ratio of induced TNAP to endogenous TNAP could be a reliable criterion. The results give evidence that hBMSC cultures are stable until passage 7 without substantial loss of differentiation potential and that established differentiation protocols lead to osteoblast-like cells but not to fully authentic osteoblasts.